Forming Integral Readers: Current Challenge of Education - Sánchez Peláez, Hugo (Espergesia, 2016)
Forming more human and happier people should be the aspiration of education in our country. Reading is one of the necessary tools to achieve it, but unfortunately low levels of reading comprehension are being reached today (PISA and PIRLS reports). This problem becomes much more serious if we take into account the real meaning of the word reading, as the activity we perform when we not only place ourselves in front of a textbook to “talk” and to interpret it, but also in front of a fact, a natural phenomenon, a living organism, an inorganic element or in front of ourselves. Reflection, in this sense, allows us to propose other meanings and sources of reading whose interpretation is and is not, at the same time, within our reach. Many of our ancestral cultures, such as Moche, Chimu and Inca, did not have textbooks to read. Therefore, how did they get to become so developed? Presumably, they used other sources of reading that for us are still hidden hoping to be synergized to form the integral reader, which is the proposal contained in the present essay. In this sense, in addition to textual books, the other sources are the world of the environments and contexts, the nature, images, the virtual world, mass media, personal inner world and the cosmological world. These are mega open books with pages full of information waiting for us to read.